Cover Image. (12th June 2020) - Jayendiran, Raja; Condemi, Francesca; Campisi, Salvatore; Viallon, Magalie; Croisille, Pierre; Avril, Stéphane
Abstract : The cover image is based on the Original Article Computational prediction of hemodynamical and biomechanical alterations induced by aneurysm dilatation in patient‐specific ascending thoracic aortas by Stéphane Avril, Raja Jayendiran, Francesca Condemi, et al., https://doi.org/10.1002/cnm.3326 .